UJI AKTIVITAS SALEP EKSTRAK DAUN JAMBU AIR (Syzygiumsemarangense) DENGAN BASIS HIDROKARBON TERHADAP PENYEMBUHAN LUKA SAYAT PADA KELINCI - Rismawati Suci Safitri; Supriyanto; Wahyu Purwanjani (Joseph: Journal of Science and Pharmacy, 2023)
Background: Water guava leaves contain chemical compounds in the form of alkaloids, flavonoids, saponins and tannins which are effective in healing wounds. Water guava leaves are used in several countries, including Indonesia, where they are used as a traditional medicine for healing wounds. Objective: To determine the hydrocarbon ointment base of water guava leaves (Syzygium semarangense) which can provide activity in healing cuts in rabbits. Method: Water guava leaf extract was obtained using the meseration method, then thickened and carried out a phytochemical screening test and thin layer chromatography to determine the compound content of water guava leaf extract which functions for healing cut wounds. Then it is formulated in the form of an ointment and the physical quality of the ointment is tested including organoleptic test, homogeneity, pH test, spreadability test, adhesiveness test, viscosity test, and ointment type test. Making an ointment formulation using water guava leaf extract using 3 (three) test animals with 5 (five) treatment groups, namely water guava leaf extract ointment with 10%, 15% and 20% hydrocarbon base, negative control with ointment base, control positive for povidone iodine 10%. All rabbits were injured with a wound length of 2 cm with a depth of ± 0.2 cm. The wound was smeared 3 times a day with the tested ointment. Wound observations were carried out every day (days 0 to 14). Data analysis was carried out using One-Way ANOVA.Results: The results of phytochemical screening tests and thin layer chromatography show that water guava leaves contain alkaloids, flavonoids, tannins and saponins. The formulation of water guava leaf extract ointment with a hydrocarbon base meets the physical quality test requirements for ointments such as organoleptic tests, homogeneity, pH, spreadability, stickiness, viscosity and the type of ointment produced is A/M, except for the spreadability at a concentration of 20% due to the addition The higher concentration of cera alba and vaseline causes the  spreadability of the ointment to become lower. The wound narrows, forms a scab and closes the wound. The statistical test results had a significant effect on wound healing in rabbits, namely (p<0.05). Conclusion: Providing an ointment with ethanol extract of water guava leaves (Syzygium semarangense) with a hydrocarbon base at a concentration of 10% provides the most optimal effect on healing cuts in rabbits.